Psychological review. - Baldwin, James Mark 1861-1934; Cattell, James McKeen 1860-1944; Warren, Howard C. 1867-1934 (Howard Crosby); Watson, John B. 1878-1958 (John Broadus); Langfeld, Herbert Sidney 1879-; Pratt, Carroll C. 1894- (Carroll Cornelius); Newcomb, Theodore Mead 1903-
Issues for 1894-1903 include the section: Psychological literature.